Learn HTML5 and JavaScript for Android - Williams, Gavin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Learn HTML5 and JavaScript for Android teaches the essential HTML5 and JavaScript skills you need to make great apps for the Android platform and browser. This book guides you through the creation of a mobile web app. You'll put the HTML5, CSS3 and JavaScript skills you learn into practice, giving you invaluable first-hand experience that will serve you well as you go on to develop your own web apps for Android smartphones and tablets. Throughout this book, you will learn new skills and bring these altogether to create a web app that runs on the Android platform as well as other mobile platforms.
Keywords: Computer science; Computer Science; Computer Science, general